2022
DOI: 10.3390/su141912551
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Disaster Training Schema Based on Team Role-Playing

Abstract: The prevalence of inevitable natural and social disasters is increasing at an alarming rate. With the proliferation of media and Internet technologies, there is a growing awareness of the importance of disaster training. The paper aims to combine the techniques of immersive Virtual Reality (VR) and team-based role-playing to demonstrate a comprehensive disaster training schema to help participants practice safety skills and learn proper decision-making skills in the face of disasters. A VR dome and cylinder co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Moreover, to test the appropriateness of IVR in specific fields some studies created literature reviews. The main outcome of these studies is that "IVR serious games look appropriate for various fields and they would result in usually meaningful learning gains and positive perceptions" (Alrehaili & Al Osman, 2019;Boel et al,2023;Chittaro & Buttussi, 2015;Dong et al, 2023;Hara et al, 2021;Jagger et al, 2015;Lamb et al, 2018;Xu & Dai, 2022). For example, it is reported that IVR has a potential in fire service education (Williams-Bell et al 2014), medical education (Lorenzo-Alvarez et al ,2019), emergency situation education (Liu et al, 2023), nursery education (Hara et al, 2021), aircraft emergency education (Chittaro & Buttussi, 2015) and business ethics education (Jagger et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, to test the appropriateness of IVR in specific fields some studies created literature reviews. The main outcome of these studies is that "IVR serious games look appropriate for various fields and they would result in usually meaningful learning gains and positive perceptions" (Alrehaili & Al Osman, 2019;Boel et al,2023;Chittaro & Buttussi, 2015;Dong et al, 2023;Hara et al, 2021;Jagger et al, 2015;Lamb et al, 2018;Xu & Dai, 2022). For example, it is reported that IVR has a potential in fire service education (Williams-Bell et al 2014), medical education (Lorenzo-Alvarez et al ,2019), emergency situation education (Liu et al, 2023), nursery education (Hara et al, 2021), aircraft emergency education (Chittaro & Buttussi, 2015) and business ethics education (Jagger et al, 2015).…”
Section: Resultsmentioning
confidence: 99%